Rationale of the BREAst cancer e-healTH [BREATH] multicentre randomised controlled trial: An Internet-based self-management intervention to foster adjustment after curative breast cancer by decreasing distress and increasing empowerment - van den Berg Sanne W; Gielissen Marieke F M; Ottevanger Petronella B; Prins Judith B (BMC Cancer, 2012)
Abstract Background After completion of curative breast cancer treatment, patients go through a transition from patient to survivor. During this re-entry phase, patients are faced with a broad range of re-entry topics, concerning physical and emotional recovery, returning to work and fear of recurrence. Standard and easy-accessible care to facilitate this transition is lacking. In order to facilitate adjustment for all breast cancer patients after primary treatment, the BREATH intervention is aimed at 1) decreasing psychological distress, and 2) increasing empowerment, defined as patients’ intra- and interpersonal strengths. Methods/design The non-guided Internet-based self-management intervention is based on cognitive behavioural therapy techniques and covers four phases of recovery after breast cancer (Looking back; Emotional processing; Strengthening; Looking ahead). Each phase of the fully automated intervention has a fixed structure that targets consecutively psychoeducation, problems in everyday life, social environment, and empowerment. Working ingredients include Information (25 scripts), Assignment (48 tasks), Assessment (10 tests) and Video (39 clips extracted from recorded interviews). A non-blinded, multicentre randomised controlled, parallel-group, superiority trial will be conducted to evaluate the effectiveness of the BREATH intervention. In six hospitals in the Netherlands, a consecutive sample of 170 will be recruited of women who completed primary curative treatment for breast cancer within 4 months. Participants will be randomly allocated to receive either usual care or usual care plus access to the online BREATH intervention (1:1). Changes in self-report questionnaires from baseline to 4 (post-intervention), 6 and 10 months will be measured. Discussion The BREATH intervention provides a psychological self-management approach to the disease management of breast cancer survivors. Innovative is the use of patients’ own strengths as an explicit intervention target, which is hypothesized to serve as a buffer to prevent psychological distress in long-term survivorship. In case of proven (cost) effectiveness, the BREATH intervention can serve as a low-cost and easy-accessible intervention to facilitate emotional, physical and social recovery of all breast cancer survivors. Trial registration This study is registered at the Netherlands Trial Register (NTR2935)